Indicators of economic risks in the indicator system of the Russian financial market: dynamics and role in ensuring the country’s economic security - T. I. Demidenko; Yu. S. Zharkova; E. I. Brichka (Путеводитель предпринимателя)
The need to ensure economic security in the context of globalization is based on the stable and safe development of all spheres of society. The financial market is the most large–scale and vulnerable area of the economic life of society, in this regard, it is relevant to study the threats affecting the activities of entities in the financial market, namely the role of economic risks in the financial market as an element of ensuring the country’s economic security. The methodological instruments of the work is based on the use of general methods of scientific knowledge, used both at the empirical and theoretical level: comparison, abstraction, modeling, analysis and synthesis. The article analyzes the risk factors of the Russian financial market since 2014, which allowed us to draw conclusions and formulate possible measures to reduce risks in the financial market that can expand the country’s economic security.